Interventionen - Levine, Michael G. (Vittorio Klostermann GmbH, 2023)
Michael Levine's interventions choose key moments in the life and work of Paul Celan as their point of departure: The birth and death of Celan's first son in 1953; an examination of the traumatic structure of Georg Büchner's work in the 1960 Meridian speech; the poems to his second son Eric, with Celan feeling compelled to choose between him and his devotion to poetry during a time of personal and political crisis in 1968; and the Jerusalem poems written after the
10.5771/9783465146032
Keywords: Aufsatzsammlung; Literaturwissenschaft; Lyrik; Interpretation; Derrida; Jacques; Germanistik; Hamacher; Werner; Celan; Paul; Büchner; Georg; Meridian; Schestag; Thomas; Böschenstein; Bernhard; Mosès; Stéphane